Cryopreservation of Genipa americana seeds - Rafaela Ribeiro de Souza; Patrícia Duarte de Oliveira Paiva; Rodrigo Therezan de Freitas; Diogo Pedrosa Corrêa da Silva; Michele Valquíria dos Reis; Fernanda Carlota Nery; Renato Paiva (Revista Ciência Agronômica, 2023)
ABSTRACT Genipa americana L. is a forest species of high socioeconomic potential. However, predatory extractivism actions threaten its existence, making it necessary to adopt conservationist practices. G. americana seeds show sensitivity to desiccation and cooling, making it unfeasible for conservation by conventional methods. Thus, cryopreservation is an promising alternative for the long-term conservation of species that produce unorthodox seeds, such as the genipap. In this sense, the objective was to cryopreservation of seeds of G. americana and to evaluate the effects of desiccation and freezing on germination and establishment of seedlings. Initially, seeds were dehydrated in silica gel 0, 16, 18, 20, 22 and 24 h, and then were cryopreserved in liquid nitrogen (LN) (-196 °C) during 24 h. After thawing, the viability and germination were analyzed. Dehydrated and non-cryopreserved seeds were also analyzed. The silica gel desiccation caused a reduction in viability and germination of the seeds of G. americana. The initial seed water content was so high (47%) that storage in LN (+LN) without prior dehydration treatment resulted in seed mortality. It was verified that, the dehydration in silica gel for the minimum time 20 h (corresponding to 14% water content) provides greater freezing tolerance, allowing the successful cryopreservation. Silica gel dehydration followed by immersion in LN was shown to be highly efficient for cryopreservation of seeds of G. americana, besides germinatio after thawing, high survival rates (100%) were obtained, with growth and normal establishment of the seedlings after acclimatization.